Expression of the Wnt signaling system in central nervous system axon guidance and regeneration - Hollis, Edmund; Zou, Yimin (Frontiers in Molecular Neuroscience, 2012)
Wnt signaling is essential for axon wiring throughout the development of the nervous system in vertebrates and invertebrates. In vertebrates, Wnts are expressed in gradients that span the entire anterior-posterior axis in the spinal cord and the medial-lateral axis in the superior colliculus. In the brainstem, Wnts are expressed in more complex gradients along the anterior-posterior axis. These gradients provide directional information for axon pathfinding and positional information for topographic mapping and are detected by cell polarity signaling pathways. The gradient expression of Wnts and the coordinated expression of Wnt signaling systems are regulated by mechanisms which are currently unknown. Injury to the adult spinal cord results in the re-induction of Wnts in multiple cell types around the lesion site and their signaling system in injured axons. Reinduced Wnts form gradients around the lesion site, with the lesion site being the peak. The reinduced Wnts may be responsible for the well-known retraction of descending motor axons through the atypical kinase receptor Ryk. Wnt signaling is an appealing therapeutic target for CNS repair. The mechanisms regulating the reinduction will be informative for therapeutic design.